EFEKTIVITAS STARBUCKS COFFEE AND FARMER EQUITY (C.A.F.E.) PRACTICES TERHADAP PETANI KOPI DI SAN JOSE, KOSTA RIKA - Bayu Tri Atmajaya; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to analyze the effectiveness of Starbucks Corporate Social Responsibility (CSR) program that is Coffee and Farmer Equity (C.A.F.E.) Practices to coffee farmers in Costa Rica. The purpose of this research are to find out and to describe the impact of the C.A.F.E. Practices throughout its four programs and the effectiveness to coffee farmers in Costa Rica. The coffee industry in Costa Rica had been through tough time during 2000s, a lot of issues to concerned, mostly about environmental and social-economic. Starbucks brings their awareness about those issues and fix it by their own CSR program.This research is a qualitative research, which is done by explaining the case based on facts. Neo liberalism theory helps to analyze the role of non nation actor, which is Multinational Corporation. Another theoretical framework applied in this research are Corporate Social Responsibility theory and the effectiveness theory and also group analysis to assisting the researcher to find the answers in this case. The techniques used to collect data to study the case of library research in the form of journals, books, an official document, articles, and websites.The result of this research shows that the four programs that are Quality, Economic Transparency, Social Responsibility and Environmental Leadership in the C.A.F.E. Practices has given impacts to costa rican coffee farmers since it was established in 2004. During its first three years ran, C.A.F.E. Practices focused to help farmers improve their coffee production for the quantity and the quality as well. Environmental issues and social-economic problems decreased from year after year. The effectiveness brought impacts and achieved the main goal of the program that are make the coffee industry to ethically sourced and sustainability. Keyword(s): Effectiveness, C.A.F.E. Practices, CSR, Starbucks